Sistem Pendukung Keputusan Dalam Pemilihan Siswa-Siswi Berprestasi Menerapkan Metode SAW (Simple Additive Weighting) - Intan Meutia Sari; Lira Arum Kusumaning Thyas (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
In facing the development of the era and the era of technology that is developing rapidly at all times, the development of human resources is a top priority in national development, the position and position of students, have a very important role in the teaching and learning activities of students in order to improve student learning achievements in academic and non-academic fields, one of the things that motivates students to always develop themselves is to give an award as an outstanding student with the criteria that have been determined by the school. Temporary observations at Mustafa Private Vocational School in determining outstanding students are carried out manually. This method is considered still less effective and efficient. Based on this, a model for determining outstanding students is needed at Mustafa Private Vocational School with a more efficient and effective system. This system is designed using a decision support system through the Simple Additive Weighting (SAW) method. This system can display the ranking results of outstanding students based on the results of the SAW method calculations.